The need for standards and certification for investigative genetic genealogy, and a notice of action. (December 2022) - Gurney, David; Press, Margaret; Moore, CeCe; Rolnick, Carol I.; Hochreiter, Andrew; Bossert, Bonnie L.
Abstract: As investigative genetic genealogy (IGG) becomes a more common tool for investigating agencies to resolve cold cases and provide names to unidentified human remains, there is an urgent need for standards and a certification process for IGG practitioners. There are four broad concerns that give rise to this need: data privacy, public trust, proficiency (and agency trust), and accountability. Yet, while the need is clear, the few discussions of standards and certification thus far have been plagued by misunderstandings of IGG and poor analogs for the profession. Thus, in addition to describing the need, this article analyzes three relevant analogs for IGG standards and certification and describes the strengths and weaknesses of each. Finally, this article announces the creation of a non-profit Board of Certification for Investigative Genetic Genealogy and a framework for standards and a certification process for IGG. Highlights: Investigative Genetic Genealogy (IGG) needs standards and a certifying body. IGG is not akin to forensic science or private investigation. IGG has different goals than traditional genealogy. IGG should be subjected to a mandated self-regulation regime. A board for standards and certification in IGG has been formed.